Quarks '90 Proceedings of the International Seminar, Telavi, USSR, 14-19 May 1990 (World Scientific Pub. Co., 1991)
Quarks '90 covers various topics in the theory of elementary particles and quantum fields (including perturbative and non-perturbative QCD, sphalerons, topological field theory, strings and superstrings, physics in TeV region), astrophysics and cosmology as related to particle physics